Encyclopedia of e-commerce, e-government, and mobile commerce - Khosrowpour, Mehdi, 1951- (Idea Group Reference, 2006)
"This encyclopedia covers the 3-technologies field highlight current concepts, trends, challenges and applications"--Provided by publisher.